Phytobezoars In A Hog Deer (Hyelaphus Porcinus) - Kumar, Vijay; Rastogi, Sameer; Dhar , A. Raj, P. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Bezoar means a concretion found in the alimentary canal of an animal especially ruminants. There are different types of bezoar known as trichobezoar (hairball), trichophytobezoar (hair and vegetable fiber) and phytobezoar (plant fiber). Obstruction by these materials can lead to indigestion, absence of defecation, development of toxaemia and ultimately death. A number of abnormal objects such as wide range of foreign bodies including bezoars present in the gastro intestinal tract of large and small ruminants (Martins, 2004 ; Remi-Adewunmi et al., (2004). Phytobezoars have been reported to be fatal in bullocks, small ruminants and wild animals (Veeraiah, 2008). The present communication reports a case of phytobezoar in the rumen of Hog deer in captivity leading to its death.